Pregnancy loss and risk of incident CVD within 5 years: Findings from the Women's Health Initiative - Wright, Catherine E.; Enquobahrie, Daniel A.; Prager, Sarah; Painter, Ian; Kooperberg, Charles; Wild, Robert A.; Park, Ki; Sealy-Jefferson, Shawnita; Kernic, Mary A. (Frontiers in Cardiovascular Medicine, 2023)
Background Prior studies have demonstrated an increased risk of cardiovascular disease (CVD) in women with a history of pregnancy loss. Less is known about whether pregnancy loss is associated with age at CVD onset, but this is a question of interest, as an association of pregnancy loss with early-onset CVD might provide clues to the biological basis of the association, as well as having implications for clinical care. We conducted an age-stratified analysis of pregnancy loss history and incident CVD in a cohort of postmenopausal women aged 50-79. Methods Associations between pregnancy loss and incident CVD were examined among participants in the Women’s Health Initiative. Exposures were any history of pregnancy loss, recurrent loss, and history of stillbirth. Logistic regression analyses were used to examine associations between pregnancy loss and incident CVD in three age strata (50-59, 69-69, 70-79). Outcomes were total CVD, coronary heart disease (CHD), congestive heart failure, and stroke. Cox proportional hazard regression was used to examine incident CVD prior to age 60 in a subset of subjects age 50-59. Results After adjustment for cardiovascular risk factors, history of stillbirth was associated with risk of all outcomes in the study cohort within 5 years of study entry. Interactions between age and pregnancy loss were not significant for any outcome; however, age-stratified analyses demonstrated an association between history of stillbirth and risk of incident CVD in all age groups, with the highest point estimate seen in women aged 50-59 (OR 1.99; 95% CI, 1.16-3.43). Stillbirth was also associated with incident CHD among women aged 50-59 (OR 3.12; 95% CI, 1.33-7.29) and 60-69 (OR 2.06; 95% CI, 1.24-3.43), and with incident heart failure and stroke among women aged 70-79. Among women aged 50-59 with a history of stillbirth, a nonsignificantly elevated hazard ratio was observed for heart failure prior to age 60 (HR 2.93, 95% CI, 0.96-6.64). Conclusions History of stillbirth was strongly associated with risk of cardiovascular outcomes within 5 years of baseline in a cohort of postmenopausal women. History of pregnancy loss, particularly stillbirth, may be a useful marker of cardiovascular disease risk in women.